Short Guanidinium‐Functionalized Poly(2‐oxazoline)s Displaying Potent Therapeutic Efficacy on Drug‐Resistant Fungal Infections. (28th February 2022) - Jiang, Weinan; Zhou, Min; Cong, Zihao; Xie, Jiayang; Zhang, Wenjing; Chen, Sheng; Zou, Jingcheng; Ji, Zhemin; Shao, Ning; Chen, Xin; Li, Maoquan; Liu, Runhui
Abstract: New antifungals are urgently needed to combat invasive fungal infections, due to limited types of available antifungal drugs and frequently encountered side effects, as well as the quick emergence of drug‐resistance. We previously developed amine‐pendent poly(2‐oxazoline)s (POXs) as synthetic mimics of host defense peptides (HDPs) to have antibacterial properties, but with poor antifungal activity. Hereby, we report the finding of short guanidinium‐pendent POXs, inspired by cell‐penetrating peptides, as synthetic mimics of HDPs to display potent antifungal activity, superior mammalian cells versus fungi selectivity, and strong therapeutic efficacy in treating local and systemic fungal infections. Moreover, the unique antifungal mechanism of fungal cell membrane penetration and organelle disruption explains the insusceptibility of POXs to antifungal resistance. The easy synthesis and structural diversity of POXs imply their potential as a class of promising antifungal agents. Abstract : Inspired by cell‐penetrating peptides, guanidinium‐pendent poly(2‐oxazoline)s were designed as synthetic mimics of host defense peptides to display potent antifungal properties, owing to the enhanced penetrating efficiency into fungal cells. Short guanidinium‐pendent poly(2‐oxazoline)s display strong therapeutic potential as a class of promising antifungal agents.